Pemberdayaan Masyarakat Desa Terhadap Prospek Unggulan Jambu Gondangmanis Menjadi Desa Wisata (Di Desa Gondangmanis, Kec. Bandar KedungMulyo, Kab. Jombang) - Eny Dyah Yuniwati; M. Dullah; M Cholil; Yulianita Verlandes (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
Gondangmanis guava production decreases every year, this is caused by pests and plant diseases, due to decreased soil quality, and soil fertility. In addition there are no good cultivation techniques so that Gondangmanis guava only grows conventionally. The purpose of this activity, for assistance, training and development of Gondangmanis guava picking tourism village. Implementation activities begin from April 2019 until August 2019, in Gondangmanis Village, kec. Bandar kedungmulyo, Jombang. The method used is a demonstration plot, and in-depth interviews. From the results of the assistance in this 3rd year, it can be concluded that there has been assistance, training and cultivation of Gondangmanis guava production. Community participation, especially those involved in guava development activities, and utilization of livestock waste is very high. Likewise, support from community leaders and village and district level officials was very supportive. Also pioneered the formation of tourism Gondangmanis guava village. The Guava Gondangmanis Community Group and the Tourism Awareness Group (POKDARWIS) have been formed. The role of the Department of Agriculture and Animal Husbandry and the Regional Government of Bappeda in Jombang Regency is also very high, because during the preparation and coordination process, it always receives attention from the leadership of the Regional Government, as evidenced by the formation of leading tourism in Jombang.